A Validated Reverse Phase HPLC Analytical Method for Quantitation of Glycoalkaloids in Solanum lycocarpum and Its Extracts - Renata Fabiane Jorge Tiossi; Mariza Abreu Miranda; João Paulo Barreto de Sousa; Fabíola Silva Garcia Praça; Maria Vitória Lopes Badra Bentley; James Dewey McChesney; Jairo Kenupp Bastos (Journal of Analytical Methods in Chemistry)
Solanum lycocarpum (Solanaceae) is native to the Brazilian Cerrado. Fruits of this species contain the glycoalkaloids solasonine (SN) and solamargine (SM), which display antiparasitic and anticancer properties. A method has been developed for the extraction and HPLC-UV analysis of the SN and SM in different parts of S. lycocarpum, mainly comprising ripe and unripe fruits, leaf, and stem. This analytical method was validated and gave good detection response with linearity over a dynamic range of 0.77–1000.00 μg mL−1 and recovery in the range of 80.92–91.71%, allowing a reliable quantitation of the target compounds. Unripe fruits displayed higher concentrations of glycoalkaloids (1.04% ± 0.01 of SN and 0.69% ± 0.00 of SM) than the ripe fruits (0.83% ± 0.02 of SN and 0.60% ± 0.01 of SM). Quantitation of glycoalkaloids in the alkaloidic extract gave 45.09% ± 1.14 of SN and 44.37% ± 0.60 of SM, respectively.